Lotus effect and biorobots: Эффект лотоса и биороботы - Даулетбекова , A. К.; Шварц, К.; Сорокин , М. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Эффект лотоса и биороботы